Using Technology to Engage Students and Build Learning Communities to Inform Instructional Decisions - Carol Todd; Victoria Anyikwa; Nancy Ryan; Patricia Tobin; Nancy Wood (Athens Institute for Education and Research, 2014)
Saint Leo University is a liberal arts university located in southwest Florida. University campus is a residential campus that teaches the traditional aged student. The campus population is 1,800 students who are mostly Florida residents, with international students representing 18 different countries. Twenty-one centers located in seven states support non-traditional student populations that may be civilian or military. The Center for Online Learning (COL) enrolls over 3,000 students who earn bachelor and masters' degrees. The School of Education and Social Services offers undergraduate and graduate programs on campus, in centers and online in criminal justice, education, human services and social work. Throughout the university and the School of Education and Social Services core values are infused in all classes. In this session faculty who teach undergraduate and graduate classes in education, social services and human services will present how they infuse emerging technologies to design and implement instruction. Panel members will discuss effective strategies in technology, utilized across disciplines, to facilitate learning and build successful community, whether the class setting be an online platform, face-to-face or blended class. The panel will share how they quantitatively and qualitatively assess the effectiveness of the diverse technologies to support student learning modalities, critical thinking and application of course content. The panel's discussion will convey the ways in which they promote dynamic student interactions and collaborations with instructors and peers. Speakers will provide a summary of how they use this information to inform instructional decisions within their specific disciplines which results in deeper understanding of course content.